Comparison of Miniperc and Standard Percutaneous Nephrolithotomy in the Treatment of Renal Stone: An Open Level Parallel Arm Randomized Control Trial - Alam, SM Syeed Ul; Rahman , Ayesha; Rassell, Md; Haque, Abul Hasanat Muhammad Afzalul; Talukder, Abdur Rabban (Journal of Current and Advance Medical Research, 2023)
Background: Treatment of renal stone is very crucial for the outcomes of the patients. Objective: The purpose of the present study was to compare the Miniperc and standard percutaneous nephrolithotomy in the Treatment of Renal Stone. Methodology: This randomized control trial was conducted in the Department of Urology at National Institute of Kidney Diseases and Urology, Dhaka and some private hospitals in Dhaka city of Bangladesh from July 2016 to November 2017 for a period of one and half year. Patients from 18 to 65 years of age with renal calculi ( 2cm) were selected on the basis of plain X-ray and ultra-sonogram of KUB region, from Urology outpatient Department (OPD) in National Institute of Kidney Diseases and Urology (NIKDU), Dhaka and some private hospitals in Dhaka city. Patients were selected in every alternate sequence (odd numbers for Miniperc in Intervention group and even numbers for Standard PCNL, control group). All patients underwent PCNL of both the procedures under general anesthesia and received intravenous broad spectrum antibiotics. Results: A total number of 60 patients were selected for study of which 30 patients were underwent miniperc and 30 patients were undergoing standard PCNL. The mean age of miniperc group and PCNL group were 34.43±11.09 and 36.70 ± 12.27 years respectively. An overall stone clearance rates was 93.33 (28) in intervention group and 6.67 % (2) was not cleared. Among the control group an overall stone clearance rates were 96.67% (29) and 3.33% (1) was not cleared. Stone clearance rates were not significant. The mean operative time (min) of intervention group was 97.47±15.03 and the mean operative time (min) of control was 86.37±17.73 Operative time was significant between the groups (p<0.05). Conclusion: In conclusion the rate of clearance of intervention group is not statistically significant. Journal of Current and Advance Medical Research, January 2023;10(1):19-24